Indeks Kerentanan Seismik di Kecamatan Pantai Cermin Menggunakan Data Mikrotremor - Agustia, Agustia; Akmam, Akmam (Journal of Science, Technology, and Innovation, 2025)
This study assesses seismic vulnerability in Pantai Cermin District, West Sumatra, using microtremor measurements analyzed through the Horizontal to Vertical Spectral Ratio (HVSR) method. Ambient vibration data were systematically acquired to characterize local site effects by deriving dominant frequency (f₀) and amplification factor (A₀), which reflect the dynamic behavior of near-surface soil layers. These parameters were integrated to compute the seismic vulnerability index (Kg) as an indicator of potential soil deformation under seismic loading. The results reveal pronounced spatial variability in f₀, A₀, and Kg values, strongly controlled by geological conditions. Areas dominated by young alluvial deposits and unconsolidated sediments exhibit low dominant frequencies, high amplification, and elevated Kg values, indicating high susceptibility to seismic ground motion amplification. Conversely, zones underlain by compact volcanic and intrusive rocks show more stable seismic responses. The spatial correspondence between high Kg zones and densely populated areas highlights increased seismic risk due to the interaction between site effects and exposure. The consistency between HVSR characteristics, geological framework, and vulnerability patterns demonstrates the robustness of the microtremor-based approach for seismic microzonation. This study provides a scientific basis for risk-informed land-use planning and earthquake mitigation strategies in seismically active regions.